2012
DOI: 10.4314/ijbcs.v5i5.8
|View full text |Cite
|
Sign up to set email alerts
|

Integrated control of <em>Striga hermonthica</em> (Del.) Benth. in Burkina Faso through host plant resistance, biocontrol and fertilizers

Abstract: A two-year field study investigated integrated management of Striga hermonthica on sorghum through host crop resistance, biocontrol (Fusarium oxysporum isolate 34-FO), and fertilizer application. The experiment was conducted in a field with natural Striga infestation at Kouaré Research Station in Fada N'Gourma, Burkina Faso. Treatments combining sorghum resistance with Fusarium inoculum and N-fertilizer or manure significantly reduced emerged Striga plant number, plant vigour and dry biomass of Striga and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 15 publications
(21 reference statements)
0
1
0
Order By: Relevance
“…It implies that Striga is known as an indicator of low soil fertility. To minimize the negative effect of Striga attack in cereals, mineral nutrients should be applied in soil (Yonli et al, 2011). Research findings (Kim et al, 1997;Pageau et al, 2003) showed that fertilizer has direct or indirect effect on Striga infection.…”
Section: Effect Of Microdosing On Striga Sppmentioning
confidence: 99%
“…It implies that Striga is known as an indicator of low soil fertility. To minimize the negative effect of Striga attack in cereals, mineral nutrients should be applied in soil (Yonli et al, 2011). Research findings (Kim et al, 1997;Pageau et al, 2003) showed that fertilizer has direct or indirect effect on Striga infection.…”
Section: Effect Of Microdosing On Striga Sppmentioning
confidence: 99%